2013
DOI: 10.1021/nl401590g
|View full text |Cite
|
Sign up to set email alerts
|

Low-Loss, Extreme Subdiffraction Photon Confinement via Silicon Carbide Localized Surface Phonon Polariton Resonators

Abstract: Plasmonics provides great promise for nanophotonic applications. However, the high optical losses inherent in metal-based plasmonic systems have limited progress. Thus, it is critical to identify alternative low-loss materials. One alternative is polar dielectrics that support surface phonon polariton (SPhP) modes, where the confinement of infrared light is aided by optical phonons. Using fabricated 6H-silicon carbide nanopillar antenna arrays, we report on the observation of subdiffraction, localized SPhP res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
378
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 289 publications
(396 citation statements)
references
References 59 publications
15
378
3
Order By: Relevance
“…Furthermore, while metal-based plasmonics has been successfully demonstrated in the UV to NIR spectral range, the very large negative permittivity at longer wavelengths limits its usefulness beyond the NIR. These issues have initiated a wide array of research into alternative, low-loss optical materials capable of supporting plasmonlike modes and/or exhibiting optical properties conducive to sub-diffraction confinement in the IR to terahertz (THz) spectral ranges [17][18][19][20][21][22][23][24][25]. The search for alternative materials for nanophotonic and metamaterial applications can be broken into two major research thrusts: 1) identifying novel, lowerloss, free-carrier-based plasmonic materials and 2) exploring the use of dielectric materials.…”
Section: Introduction To Surface Phonon Polaritonsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, while metal-based plasmonics has been successfully demonstrated in the UV to NIR spectral range, the very large negative permittivity at longer wavelengths limits its usefulness beyond the NIR. These issues have initiated a wide array of research into alternative, low-loss optical materials capable of supporting plasmonlike modes and/or exhibiting optical properties conducive to sub-diffraction confinement in the IR to terahertz (THz) spectral ranges [17][18][19][20][21][22][23][24][25]. The search for alternative materials for nanophotonic and metamaterial applications can be broken into two major research thrusts: 1) identifying novel, lowerloss, free-carrier-based plasmonic materials and 2) exploring the use of dielectric materials.…”
Section: Introduction To Surface Phonon Polaritonsmentioning
confidence: 99%
“…However, most of these potential applications have been limited by poor efficiencies, the requirement of cryogenic cooling, and/or by inefficient or the complete absence of monochromatic, coherent sources. Similar to efforts with plasmonic materials in the UV-Vis range, the high local electromagnetic fields and large potential Purcell factors from SPhP systems [23] should provide direct avenues towards enhancing these optical processes and thus enabling the next generation of optical devices. Prior work has also demonstrated that tailored thermal emission from SPhP modes within subwavelength SiC wires provided polarized, narrow-band sources [51].…”
Section: Introduction To Surface Phonon Polaritonsmentioning
confidence: 99%
“…In recent years, there has been considerable interest in the mid-infrared Reststrahl 1 spectral region of Silicon Carbide (SiC), [2][3][4][5][6] since it holds much promise for a novel approach to low-loss, mid-infrared (IR) nanophotonic applications based on surface phonon polaritons (SPhPs). 4,5 Similarly to surface plasmon polaritons in metals, these surface phonon waves in the Reststrahl band of polar dielectrics can be tailored using resonant optical nano-antennas 4,5 as the fundamental building block of future nanophotonic devices.…”
mentioning
confidence: 99%
“…4,5 Similarly to surface plasmon polaritons in metals, these surface phonon waves in the Reststrahl band of polar dielectrics can be tailored using resonant optical nano-antennas 4,5 as the fundamental building block of future nanophotonic devices. 7,8 Most importantly, nanophotonics based on SPhPs could solve the intrinsic optical loss-problem of plasmonics, 9 making use of the much smaller damping rates of phonons as compared to plasmons.…”
mentioning
confidence: 99%
“…This is mainly due to the huge number of applications nanoplasmonics can offer 7,8 . These range from solar cells efficiency improvement 9,10 , to surface enhanced Raman spectroscopy 11 , sub-diffraction photon confinement 12,13 , bio-sensing 14,15 , non linear phenomena 16 , nano-antenna for light-emitting devices [17][18][19] , and quantum cascade lasers 20 .…”
Section: Introductionmentioning
confidence: 99%